The Formulation of Binding Agent Concentration on Raw Restructured Goat Meat Trimming Product - Rini Mastuti (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2008)
The utilization of raw materials and formulation method would affect the quality of the processed meat product. Therefore, a research on the processing method to produce a raw structured product should be conducted. The research was testing a single factor comprises of following parameters: control (without) binding agent; 0.3%, 0.5% and 0.7% sodium alginat and 0.3%, 0.5% and 0.7% carragenan, respectively. The results showed that the goat meat trimming could be used as raw materials in the production of the best restructured meat using 0.5% carragenan. This raw restructured meat produced had a loss weight of 1.67%, pH value  7.89, WHC  48.345, and moisture content  75.20%.   Keywords : sodium alginat, carragenan, raw restructured goat meat trimming.